Pengaruh Struktur Corporate Governance Terhadap Kinerja Perusahaan Publik Indonesia - Rafrini Amyulianthy (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2012)
This study required to test the influence of corporate governance structure that includes an independent board, the board of directors, institutional ownership and managerial ownership on firm’s value in Indonesia. The sample in this study were 45 companies included and registered as a company with the most liquid stocks (LQ-45) on the Stock Exchange during the period January 2010 to December 2010. The data used in this study is a secondary data contained in the Indonesian Capital Market Directory and the annual reports obtained from the Data Centre for Economics and Business at the University of Indonesia. The data collected, processed by using procedures Ordinary Least Square (OLS) using multiple regression. This study found that corporate governance structure that includes an independent board, the board of directors, institutional ownership and managerial ownership has a significant impact on firm’s value.